Project Management Performance Improvement Using Maturity Model at Architecture Firm - Meirani Kusuma, Atika; Bekti, Rudy (The Indonesian Journal of Business Administration, 2016)
Abstract - The degree of competition, complexity and uncertainty are high in construction industy. It was observed that the occurrence of unexpected events and changes has caused consequential problems arise throughout the project. In 2015, PT. Penta Rekayasa could manage a good customer satisfaction rate, but the organization experinced over budget in 66.67% of overall and over manhour per drawing in 22.22% of overall project. It is known that organizations that are not mature can still deliver outstanding results but at the same time have other projects that could not be performing well. It is becoming important to understand current maturity level of project management and highlights the key areas as the baseline to make continuous performance improvements. The aims of this research are to assess the current maturity level of PT. Penta Rekayasa and generating effective improvements recommendation in project management area to improve the business performance. To assess the current maturity level, this research using maturity model that focuses on process perspectives with its embedded generic attributes. Those perspectives and attributes are assessed at five maturity level. It allows PT. Penta Rekayasa to have its methods and processes assessed according to management best practice. Gap analysis also used to identify key areas as the baseline for affective improvement. After conducting the assessment and analysis, it is discovered that PT. Penta Rekayasa has level 2 in its project management maturity, which means that the organization has managed its project with various project management frameworks, however, its processes and procedures are running in minimum standard. There is inconsistency of organizational guidance and current performance lacks concept realization. There are prioritized key areas that are needed to improve such as, risk management, planning and estimating, resource management, management control, scrutiny and review,.capability development, and benefits management. PT. Penta Rekayasa is recommended to acquire maturity level 3 by maturing specific processes, concepts and generic attributes in discovered key areas of improvement in order to achive a defined process level and have a consistent set of standards used with clear process owners across the organization that eventually will improve business performance.Ã‚Â Keywords: project management, maturity model, improvement, architecture firm